2017
DOI: 10.1371/journal.pone.0188425
|View full text |Cite
|
Sign up to set email alerts
|

Short-term succinic acid treatment mitigates cerebellar mitochondrial OXPHOS dysfunction, neurodegeneration and ataxia in a Purkinje-specific spinocerebellar ataxia type 1 (SCA1) mouse model

Abstract: Mitochondrial dysfunction plays a significant role in neurodegenerative disease including ataxias and other movement disorders, particularly those marked by progressive degeneration in the cerebellum. In this study, we investigate the role of mitochondrial oxidative phosphorylation (OXPHOS) deficits in cerebellar tissue of a Purkinje cell-driven spinocerebellar ataxia type 1 (SCA1) mouse. Using RNA sequencing transcriptomics, OXPHOS complex assembly analysis and oxygen consumption assays, we report that in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 61 publications
1
40
0
1
Order By: Relevance
“…Table S28). To validate results of previous study pointing out the reduced complex I/maximal respiration ratio in the cerebellum of the SCA1 mice 23 , we performed the same analysis with negative results (P = 0.44).…”
Section: Hippocampal Atrophy Precedes Cerebellar Degeneration and Refmentioning
confidence: 76%
See 2 more Smart Citations
“…Table S28). To validate results of previous study pointing out the reduced complex I/maximal respiration ratio in the cerebellum of the SCA1 mice 23 , we performed the same analysis with negative results (P = 0.44).…”
Section: Hippocampal Atrophy Precedes Cerebellar Degeneration and Refmentioning
confidence: 76%
“…In addition to hippocampal atrophy and the related behavioral deficits, we also identified corresponding mitochondrial dysfunction in the hippocampus (but not in the cerebellum) of the young SCA1 mice. Although mitochondrial dysfunction comprises one of a number of common pathological mechanisms shared by various neurodegenerative diseases 19 , it has been studied only rarely in spinocerebellar ataxias focusing exclusively on cerebellar tissue/cells [23][24][25] . The fact that we did not determine any mitochondrial dysfunction in the cerebellum contradicts the results of previous studies 23, 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are inconsistent with major mitochondrial defects occurring in HD. Although not a feature of early disease in SCA1, studies in a mouse model demonstrated reduced mitochondrial transcripts and protein during the course of disease (111). In transgenic mouse models of SCA3, mitochondrial DNA depletion is seen in affected neuronal regions (112).…”
Section: Mitochondrial Functionmentioning
confidence: 99%
“…Окисляясь сукцинатдегидрогеназой, янтарная кислота в дыхательной цепи обеспечивает быстрый ресинтез АТФ клетками [22] и более выраженно, чем другие субстраты цикла Кребса, повышает количество восстановленных митохондриальных никотинамиддинуклеотидов (НАД+) [23]. Введение янтарной кислоты при некоторых экспериментальных моделях нейродегенеративных заболеваний приводит к быстрому снижению митохондриальной дисфункции и уменьшению неврологического дефекта [24].…”
Section: метаболические эффекты цитофлавинаunclassified